2018
DOI: 10.7759/cureus.3072
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of a Robotic Operative Microscope - Visualization Platform for Neurosurgery

Abstract: BackgroundWe assessed a new robotic visualization platform with novel user-control features and compared its performance to the previous model of operative microscope.MethodsIn a neurosurgery research laboratory, we performed anatomical dissections and assessed robotic, exoscopic, endoscopic, fluorescence functionality. Usability and functionality were tested in the operating room over 1 year.ResultsThe robotic microscope showed higher sensitivity for fluorescein sodium, higher detail in non-fluorescent backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
0
26
0
7
Order By: Relevance
“…The Gen2 CLE device was designed to function specifically for intraoperative application in neurosurgery and to integrate with the robotic operating microscope visualization platform for neurosurgery (22). The goals for this device in neurosurgery are ultimately to increase the positive yield of biopsies and to serve as a tool to microscopically explore, in portable and rapid fashion, for tumor cells beyond the obvious margin of infiltrating tumors, such as cells in and around the surgical resection bed, or to define suspected tumor invasion within eloquent cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The Gen2 CLE device was designed to function specifically for intraoperative application in neurosurgery and to integrate with the robotic operating microscope visualization platform for neurosurgery (22). The goals for this device in neurosurgery are ultimately to increase the positive yield of biopsies and to serve as a tool to microscopically explore, in portable and rapid fashion, for tumor cells beyond the obvious margin of infiltrating tumors, such as cells in and around the surgical resection bed, or to define suspected tumor invasion within eloquent cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, although most neurosurgeons today are accustomed to an operative microscope, there is certainly a learning curve necessary before using the exoscope in spinal surgery. Belykh et al [26] reported a signi cant learning curve exists for becoming accustomed to operating with the exoscope system. No doubt it could be a potential issue for operators who are not familiar with the comparable microscope setup.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein is a bright yellow fluorophore used off-label for tumor labeling in neurosurgery, with a growing body of evidence suggesting that its use improves achievement of gross total resection (3739). Advanced illumination capabilities of the latest operating microscopes allow neurosurgeons to work directly under the Yellow 560 filter throughout the tumor resection (40).…”
Section: Discussionmentioning
confidence: 99%